Stylistic analysis of the phonetic texture of J. K. Rowling’s novels - Leona Grigoryeva, Natalia Maklakova,; Besedina, Elena; Maklakov, Ivan (Opción, 2019)
The study aimed to analyze stylistic devices employed by J.K. Rowling in the sound organization of her eleven literary works including her Harry Potter series as well as her tragicomedy Casual Vacancy and her first three detective novels: The Cuckoo’s Calling, Silkworm and Career of Evil via quantitative analysis of linguistic data and stylistic. As a result, Rowling also employs a literary technique of transformation of word-sound images, i.e. wordplay. In conclusion, Rowling’s novels are distinguished by aesthetic excellence in her employment of the entire arsenal of phonetic stylistic devices of the English language.